2020
DOI: 10.20944/preprints202012.0383.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery and Optimization of Selective Inhibitors of Meprin α (Part II)

Abstract: Meprin α is a zinc metalloproteinase (metzincin) that has been implicated in multiple diseases, including fibrosis and cancers. It has proven difficult to find small molecules that are capable of selectively inhibiting meprin α, or its close relative meprin β, over numerous other metzincins which, if inhibited, would elicit unwanted effects. We recently identified possible molecular starting points for meprin α-specific inhibition through an HTS effort (see part I, preced… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This underpins the predicted binding mode of the heteroaromatic inhibitors from previous docking studies, that suggested one phenyl substituent being orientated towards the S1'-subsite. 37 Thus, the lack of interactions of the methyl moiety or a different orientation by the benzyl moiety within the S1'-binding site could lead to a decrease in meprin inhibition. The introduction of a cyclic moiety, directly connected to the pyrazole core is favorable for the inhibition of meprin α and β and might address the S1'-subsite like the phenyl residue found in 7a.…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…This underpins the predicted binding mode of the heteroaromatic inhibitors from previous docking studies, that suggested one phenyl substituent being orientated towards the S1'-subsite. 37 Thus, the lack of interactions of the methyl moiety or a different orientation by the benzyl moiety within the S1'-binding site could lead to a decrease in meprin inhibition. The introduction of a cyclic moiety, directly connected to the pyrazole core is favorable for the inhibition of meprin α and β and might address the S1'-subsite like the phenyl residue found in 7a.…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…7a,b & 8a,b), respectively. [36][37][38] The latter monocyclic or fused heteroaromatic derivatives represent the most potent inhibitors of meprins that have been reported to date, even without any functionalization of the actual diaryl-heteroaromatic scaffold.…”
Section: Introductionmentioning
confidence: 99%